Menopause Readiness in Perimenopausal Women in Tanjungpinang Region - Komala Sari; Hotmaria Julia Dolok Saribu; Linda Widiastuti (Sriwijaya Journal of Medicine, 2024)
Menopause is a natural phase in a woman's life that is faced with various physical and psychological changes. However, many women are not fully prepared for this transition. Lack of education and social support often affect their readiness to face menopause, especially in areas with low health literacy rates. Limited knowledge about perimenopause symptoms and how to manage them can impact a woman's quality of life during this time. This study aims to determine the level of preparedness of women in Tanjungpinang in facing menopause. Method: This study used a quantitative descriptive design. The sampling technique used was purposive sampling with a sample size of 51 women in the perimenopause age range. Data were collected through a questionnaire related to readiness to face menopause. Data analysis was carried out using descriptive statistics to describe the frequency distribution. Most respondents were in the age range of 50 years (27%), with the majority having secondary education (56.9%) and already having more than one child (86.3%). Smoking behavior was found in 96.1% of respondents. Although 54.9% of respondents felt ready to face menopause, there were still 45.1% who felt unprepared. Factors such as education level, number of children, and smoking behavior affect their readiness to face this transition. Women's readiness to face menopause in Tanjungpinang is influenced by various factors, including education, number of children, and smoking behavior. Further research is needed to identify effective interventions to improve women's readiness to face menopause, especially in diverse socio-cultural contexts.